Persepsi Guru dan Peserta Didik terhadap Proses Pembelajaran Fisika Berdasarkan Kurikulum 2013 - Suluh, Melkianus; Jumadi, Jumadi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2019)
[Title: Perception Of Teachers And Students On The Physical Learning Process Based On Curriculum 2013] This study aims to determine: (1) the perception of physics teachers to apply a scientific approach, (2) the perceptions of students on the physics learning process carried out by teachers, (3) the relationship between students' perceptions and the ability of teachers to carry out physics-based learning scientific approach. This research is a survey research using a descriptive correlational approach. The research sample included 18 physics teachers and 494 students spread across 10 Public High Schools in Yogyakarta City which were taken using a purposive sampling technique. Data collection uses questionnaires from teachers and students and observation sheets. The analysis technique uses descriptive analysis and Spearman correlation analysis. Research Results (1) The teacher has a very positive perception of the implementation of a scientific approach in scientific learning; (2) Students give a positive response to the process of physics learning carried out by the teacher; (3) There is a positive and significant relationship between the perceptions of students and the ability of teachers to carry out physics learning based on the scientific approach.